Sodobni pristop k zdravljenju multiple skleroze - Savšek, Lina (Farmacevtski vestnik, 2024)
The progression of multiple sclerosis is driven by the intertwined dynamics of immune-mediated neuroinflammation and neurodegeneration, making it the leading cause of nontraumatic neurological disability in young adults. A modern treatment approach necessitates a clear definition of the disease course, identification of prognostic factors, and early personalized intervention. The primary treatment goals focus on slowing neuroinflammation and neurodegeneration to reduce long-term disability and enhance quality of life. Although early use of high-efficacy disease-modifying treatments correlates with improved long-term outcomes, it poses higher safety risks. Factors influencing therapy choice include drug efficacy and safety, neurological disability, clinical and radiologic disease activity, comorbidities, and patient preferences, including family planning. Comprehensive knowledge of disease-modifying treatment mechanisms and monitoring protocols is crucial to mitigate associated risks.
Keywords: Multipla skleroza; Multiple sclerosis; Terapija; Therapy